A Tribute to a Mathemagician - Manasse, Mark; Sleator, Danny; Wei, Victor K.; Baxter, Nick (A. K. Peters, 2004)
The Panex puzzle is a one-person board game created by Toshio Akanuma and manufactured by TRICKS Co., Ltd. of Tokyo, Japan. On first sight, the puzzle reminds one of the Tower of Hanoi. A little thought reveals that they are intriguingly different. The puzzle consists of a flat board with three vertical tracks laid in the board with a horizontal track at the top connecting the three. The board is made of two flat pieces fastened together by screws, with intricate shapes hidden between them. Rectangular tile pieces can be moved along and inside the tracks, but cannot be lifted out of the board, nor rotated. Thus, for example, one tile cannot fly over another tile. For the Silver version (see Figure 1), there are ten tiles with blue markings, and ten with orange markings. The markings of the same color are such that they form a narrow, ten-story high triangle-shaped tower, with each tile taking up one floor (or layer). For the Gold version (see Figure 3), each tower is made up of tiles that appear identical, but otherwise is constructed identically to the Silver version.